Internal Supervision of School Administrators under Si Sa Ket Primary Educational Service Area Office 1: Internal Supervision of School Administrators under Si Sa Ket Primary Educational Service Area Office 1 - Chaiwongsa, Buaphan; Promseemai, Wilaiwan; Khantaree, Narech (RATANABUTH JOURNAL, 2026)
The objectives of this research were: 1) to study the internal supervision of school administrators under the Si Sa Ket Primary Educational Service Area Office 1; 2) to compare the internal supervision as perceived by teachers, classified by work experience and school size; and 3) to investigate guidelines for internal supervision of school administrators. The research sample consisted of 155 basic education school teachers in the 2022 academic year, with the sample size determined using the Krejcie and Morgan table. The research instrument was a 5-point Likert scale questionnaire with a total reliability coefficient of .97. Data were analyzed using percentage, mean, standard deviation, and One-Way ANOVA to test for significant differences. The research findings were as follows: 1) Overall, the internal supervision of school administrators under the Si Sa Ket Primary Educational Service Area Office 1 across all 7 dimensions was at a high level. 2) The comparative analysis of teachers’ perceptions toward internal supervision revealed that: 1) when classified by work experience, there were statistically significant differences both overall and in individual dimensions at the .05 level. Teachers with 11 or more years of experience had significantly higher perceptions of supervision practices in curriculum development and instructional management than those with less than 10 years of experience. However, regarding community relations, teachers with less than 10 years of experience demonstrated higher perceptions of supervision practices. 2) When classified by school size, statistically significant differences were also found both overall and in individual dimensions at the .05 level. 3) Guidelines for internal supervision of school administrators indicated that administrators should encourage teachers to participate in curriculum development planning, emphasize student-centered learning through the integration of technology in instructional management, develop measurement and evaluation systems based on clear indicators, maintain safe school buildings and environments, ensure financial registration records are up-to-date, strengthen the student care and support system, and continuously build collaborative networks with parents.